Managing special educational needs : a practical guide for primary and secondary schools - Gibson, Suanne; Blandford, Sonia (London, Thousand Oaks, CA : Paul Chapman Pub. ; PCP/Sage Publications, 2005)
Written from a practitioner's perspective, this book shows schools how to effectively implement and manage an inclusive school environment. Drawing from their experience in a range of schools, the authors highlight the problems encountered by professionals in both primary and secondary school settings and offer practical solutions and advice. The book offers guidance on: the role of the SENCO as a teacher and manager; government policy and legislation; self-evaluation, good practice and monitoring; how to relate SEN to school targets and development plans.
Special Educational Needs -- Devolution and Inclusion -- The School as a Community -- From the Community to the Classroom -- Leadership and Management -- External Agencies and the School Community -- A Policy for Practice -- Professional Development in an Inclusive and Effective School.
Includes bibliographical references and index.
Keywords: SCHOOL MANAGEMENT AND ORGANIZATION; SPECIAL EDUCATION